One is not enough: Monitoring microplastic ingestion by fish needs a multispecies approach. (November 2022) - Valente, Tommaso; Pelamatti, Tania; Avio, Carlo Giacomo; Camedda, Andrea; Costantini, Maria Letizia; de Lucia, Giuseppe Andrea; Jacomini, Carlo; Piermarini, Raffaella; Regoli, Francesco; Sbrana, Alice; Ventura, Daniele; Silvestri, Cecilia; et al.
Abstract: The development of monitoring programs based on bioindicators is crucial for assessing the impact of microplastic ingestion on marine organisms. This study presents results from an Italian pilot action aimed at investigating the suitability of a monitoring strategy based on a multispecies approach. The benthic-feeder Mullus barbatus, the demersal species Merluccius merluccius, and the pelagic-feeder species of the genus Scomber were used to assess the environmental contamination by microplastics in three different marine areas, namely Ancona (Adriatic Sea), Anzio (Tyrrhenian Sea), and Oristano (Western Sardinia). Microplastic ingestion frequencies were higher in samples from Anzio (26.7 %) and Ancona (25.0 %) than Oristano (14.4 %), suggesting a relationship between microplastic bioavailability and the proximity to urban settlements and river flows. Furthermore, microplastic ingestion was affected by the feeding habits of the examined species. The detected differences reinforce the hypothesis that a multispecies approach is needed to evaluate microplastic ingestion by marine animals. Highlights: Fish species are suitable bioindicators of microplastic ingestion at a local scale. The bioavailability of microplastic increases with proximity to contamination sources. Feeding habits may affect the bioavailability of different microplastic types. Microplastic ingestion events cannot be fully described by examining a single species. A multispecies approach should be developed for monitoring microplastic ingestion.